THE IMPLEMENTATION OF BLENDED LEARNING-BASED MODEL E-LEARNING MOODLE - Dona Fitriawan; Wardah Wardah (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The objectives of this study are: 1) Implementing blended learning model based on e-learning Moodle into learning; 2) whether the blended learning model based on Moodle e-learning can improve learning achievement. The type of research in this research is descriptive-explorative qualitative, which explores all the things that are in the processing of questions and answers to students' steps and explores the results of the interview survey with students. The subjects in this study were 21 class B students. The research instruments were tests, surveys, questionnaires, and interviews. The results of research and discussion show the implementation of the lecture process, face to face with zoom metting, presence in applications, assignments, and testing. From the results of the research and discussion, it is concluded that: 1) the blended learning model based on e-learning Moodle has been successfully implemented into linear learning program courses, 2) From the results of tests, questionnaires, surveys and interviews with e-based blended learning model students -learning moodle has increased their achievement and enthusiasm for learning.